Development Of Ultrasonic Scalpel - Ngo, Yi Bin (Universiti Sains Malaysia, 2019)
The usage of traditional electrosurgery devices in different field of medical disciplines consists of disadvantages such as the potential of alternatives site burn due to high current density, complexity of the operation, severe postoperative effects, and higher operation cost. An US for soft tissue dissection has been designed, prototyped, and characterized. It is used for cutting and cauterizing soft tissue. In this device, it includes power supply with ultrasonicwave-signal generator, ultrasonic transducer, ultrasonic amplifier, a pair of end effectors, and a casing with trigger mechanism. Characterization is done on the existing ultrasonic actuator to ensure it can dissect soft tissue efficiently. Conceptual design is done by using Solidworks, and the design is refined until optimum design is obtained. The prototype of the final design is done by using machining process for the metal components and rapid prototyping for the plastic parts which are finally assembled for characterization purpose. The result shows that the natural frequency of the designed US is 29.28kHz, with peak to peak vibration stroke of 40